Medical experiment conducted on human subject – aspects of international, European and national laws - Karski, Leszek (Studia Ecologiae et Bioethicae, 2013)
The article is designed to provide readers with a legal context of medical experimentation. Medical research involving humans needs careful regulation. Although international law, European law, and domestic law are usually described as separate sources of law, they are increasingly interdependent. Their interaction produces a layering effect of laws that address medical experimentation. The paper begins with an overview of the content of soft international law. In the next section, the author addresses the issue of hard law, i.e. the Geneva Conventions, provisions of the International Covenant on Civil and Political Rights and International Covenant on Economic, Social and Cultural Rights. The Convention for the Protection of Human Rights and Dignity of the Human Being with regard to the Application of Biology and Medicine is the subject of analysis in the third part of the paper. The next section discusses selected issues related to regulations of European Union law. At the national level, the Polish Constitution provides for a medical research principle. In order to provide deeper insight, the next part of the analysis is based on domestic criminal law. The final section discusses the role of the physician in medical research in light of the norm included in the 1996 Act on the professions of the physician and dentist.